Investigation of splicing changes and post-translational processing of LMNA in sporadic inclusion body myositis - Yue Bei Luo (2018)
Some features of sporadic inclusion body myositis (s-IBM) suggest that there is acceleration of the normal ageing process in muscle tissue. LMNA encodes the nuclear lamina proteins lamin A/C through alternative splicing, and aberrant splicing of exon 11 leads to the premature ageing disease, Hutchinson-Gilford progeria syndrome. Progerin, the pathogenic isoform expressed in HGPS tissues, has also been detected at low levels in tissues of normal individuals with aging. We therefore investigated the alternative splicing of LMNA gene transcripts, and the post-translational processing of prelamin A, in s-IBM and control muscle samples. Age-related low level expression of the progerin transcript was detected in both s-IBM and control muscles, but was not increased in s-IBM and there was no increase in progerin protein or demonstrable accumulation of intermediate prelamin isoforms in the s-IBM muscles. However, an age-related shift in the balance of splicing towards lamin A-related transcripts, which was present in normal muscles, was not found in s-IBM. Our findings indicate that while there are changes in the patterns of LMNA splicing in s-IBM muscle which are probably secondary to the underlying pathological process, it is unlikely that aberrant splicing of exon 11 or defective post-translational processing of prelamin A are involved in the pathogenesis of the disease.